Supporting Private Sector Development in Iraq - Rimmer, Stephen; Al-Ani, Mohammed (World Bank, Washington, DC, 2012)
While Iraq is a middle-income country it faces challenges which are more commonly found in low income countries. These include dependence on one primary commodity (crude oil); significant infrastructure reconstruction and rehabilitation needs; and poorly performing regulatory policies, institutions and processes. Iraq's recent success in stabilizing its macro economy and budget was an important step towards reversing this situation. However, much more needs to be done. For example, oil revenues generate over 95 percent of budget revenues but the oil sector employs only one per cent of the labor force. Developing a strong and healthy private sector is necessary for Iraq to develop a diversified and resilient market economy with rising living standards. Furthermore progress is needed in diversifying its economy and creating healthy competition in markets to generate employment and sustainable livelihoods for the majority of its growing population. Iraq's transition to a more diversified market economy continues to take place in a fragile political, security and institutional context.